Next-generation textiles: from embedded supercapacitors to lithium ion batteries. Issue 43 (12th October 2016) - Gulzar, Umair; Goriparti, Subrahmanyam; Miele, Ermanno; Li, Tao; Maidecchi, Giulia; Toma, Andrea; De Angelis, Francesco; Capiglia, Claudio; Zaccaria, Remo Proietti
Abstract : In this work we have reviewed the state of the art of energy storage devices for textile applications. Abstract : This review summarizes the cutting edge advances in the field of textile-based energy storage devices with particular emphasis on the nature and preparation of electrode materials for both supercapacitors and lithium ion batteries. Indeed, due to the overwhelming increase of the worldwide demand for high-tech products, energy storage has become one of the most up-to-date debating topics. In this regard, and considering also the well-known environmental issues often related to the fabrication of new energy products, it is important for the scientific community to develop new electrochemical energy storage systems based on eco-efficient synthetic processes and capable of serving the needs of the next generation of electronics. To this end, textile-based energy storage devices are emerging as a viable alternative to their conventional rigid counterparts. These devices have to be flexible, lightweight and should be compatible with futuristic miniaturized electronic gadgets. We have discussed how supercapacitors and Li-ion batteries are combined with textiles to realize flexible and wearable storage devices. The most important parameters, both from the electrochemical and textile points of view, have been taken into account in order to provide, as much as possible, a standard reference for comparing different kinds of textile-based energy storage devices. These parameters include electrode fibers configuration, fiber diameter, tensile strength, capacitance, charge/discharge capacity, Coulombic efficiency and capacity retention. Furthermore, in this review textile electrodes have been classified into two categories, according to the fabrication strategies: bottom-up and top-down fabrication processes. To conclude, the main aim of this review is to provide an organic outline of the recent research progress and perspectives on textile-based energy storage devices.